Is There a Place for the Other in Fokloristics? Ima prostora za drugog u fokloristici? - Polgar, Nataša (Studia mythologica Slavica, 2011)
An attempt will be made in this paper to identify the frameworks within which it is possible to introduce the concept of the Other into folkloristics. The Other is discussed primarily as a psychoanalytic term coined by Jacques Lacan, a notion that is very productive in the interpretation of diverse aspects of culture and folklore phenomena, which are not, for their part, fully explicable only with the help of historical, political and social factors. This paper deals with the ways in which Lacan’s categories can be used in reading narratives and oral stories about supernatural beings, especially witches. The psychological dimensions of the construction of witches have not been properly taken into consideration, although witch-trial records, narratives about witches, oral stories and Malleus Malefi carum in particular would allow such analysis. Witches are represented as an extreme, as particularly evil or harmful, as beings that undermine the social order. Their construction as the Other can be read as a means of establishing the social order, a way of maintaining and preserving cultural norms.